THE CONVERSION OF NAHDLATUL ULAMA’S (NU) AFFILIATED PEOPLE TO MAJELISTAFSIR AL-QUR’AN (MTA): A CASE STUDY FROM TRADITIONAL TO PURITAN ISLAM - Achmad Maimun (Islam Futura, 2021)
Religion is a principle that has been taught since the early age. Therefore, religion is difficult to change and even contributes to form one’s soul. However, it does not mean that one’s religious understanding or religion cannot change. Religious change, which is often synonymous with religious conversion, can be considered as the transfer of mażab (schools) or religious beliefs, such as from Nahdlatul ’Ulama (NU) to Majelis Tafsir Al-Qur’an (MTA). To explain that phenomenon, this study is conducted based on three main issues: the process of conversion from NU to MTA, the basis of its rationality, and further implications. Those issues are examined using qualitative research method, applying phenomenological approach. The following results are the research’s findings: changes on understanding from NU to MTA are often caused by one’s psychological factors, while its complementer is caused by social factors. The process of the changes does not happen suddenly, but gradually with the basis of rationality. There are seven phases of the conversion from NU to MTA, namely curiosity and crisis, quest, encounter, interaction, commitment, consequences, and deployable agent. Meanwhile, its basis of rationality consists of clarity and certainty of the basis of Islam, obedience to Al-Qur’an and al-Hadiṡ, and egalitarianism. The phenomenon of conversion may result in counterproductive effects, such as verbal violence towards the perpetrator and social exclusion. Thus, to avoid conflict, one of the important things to do is to give tasamuh education to the moslem community so that they are willing to accept differences wisely.